The Effect of Remaining Coronal Tissue Height on the Fracture Strength of Over-Flared Endodontically Treated Central Incisors Restored Using a Multipost Approach - Mahsa Farshbaf-antik; Mahdi Abed-Kahnamouei; Parnian Alizadeh-Oskoee; Narmin Mohammadi; Siavash Savadi-Oskoee (International Journal of Dentistry)
Objectives. This study aimed to examine the effect of remaining coronal tissue height on the fracture strength of over-flared endodontically treated central incisors restored with multiple prefabricated fiberglass posts using the multipost approach. Materials and Methods. A total of 40 human central maxillary incisors were examined in this study. The samples were assigned to five groups (n = 8) based on the height of the remaining coronal tissue: with no remaining coronal tissue, 1-mm coronal tissue height (CTH1), 2-mm coronal tissue height, 3-mm coronal tissue height (CTH3), and one intact tooth (IT) group. Following endodontic treatment of an over-flared canal, the postspace depth was 10 mm, and the residual dentin thickness was 1 mm. Two prefabricated fiberglass posts were cemented into the root canal, adopting a multipost approach. The static load was applied at 0.5 mm/min and 135° concerning the tooth’s longitudinal axis until a fracture occurred. One-way analysis of variance and the post hoc Tukey’s test were performed to analyze the data at a significance level of p<0.05. Results. The maximum fracture strength was recorded for IT (control group), while the minimum fracture strength was found for teeth with a coronal tissue height of 1 mm. The differences between IT group and other groups (p<0.05), as well as the differences between the group with CTH3 and groups without coronal tissue and CTH1, were significant. Conclusion. In sum, an increase in the height of the remaining coronal tissue (≥3 mm) significantly increased the fracture strength of over-flared endodontically treated central incisors after restoration with prefabricated fiberglass posts by adopting a multipost approach.